Pengembangan Media Pembuatan Sulaman Pita Dengan Menggunakan Video Pada Mata Pelajaran Pembuatan Hiasan Busana Kelas Xi Di Sekolah Menengah Kejuruan Negeri 2 Godean Yogyakarta Tahun Pelajaran 2023/2024 - Khairunnisa, Afifah; Karyaningsih, Endang Wani; Setyaningsih, Rina (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sarjanawiyata Tamansiswa, 2024)
This research and development aims to determine: 1) the development of media for making ribbon embroidery using video, 2) the feasibility of media for making ribbon embroidery using video, and 3) students' responses to the media for making ribbon embroidery using video. The development model used in this research uses the Four-D model which consists of 5 stages, namely define, design, development and disseminate. The results of this research and development show that the feasibility level of media experts is 97.29% (very feasible) and material experts are 98.90% (very feasible). The small scale trial got a result of 91.66% (strongly agree) and the limited scale trial got a percentage of 85.17% (strongly agree).